Is green finance fostering high-quality energy development in China? A spatial spillover perspective - Jiajun Xu; Jinchao Wang; Rui Li; Muxin Gu (Energy Strategy Reviews, 2023)
As the world's largest energy consumer, it is worth exploring how China can achieve high-quality energy development. This paper aims to assess the role of green finance development in China's high-quality energy development (HED). We develop two indicator systems to measure the level of provincial green finance and HED in China and find a significant contribution of green finance to both local and neighboring HED based on a spatial model. These findings still hold after considering endogeneity and performing a series of robustness tests. In addition, we find that the effect of green finance is more pronounced after exceeding the threshold value, and the spatial spillover boundary of green finance is 1750 km. These findings provide a reference for the government to develop further green finance policies to achieve high-quality energy development.